The Role of Airway and Endobronchial Ultrasound in Perioperative Medicine - Votruba, Jiri; Zemanová, Petra; Lambert, Lukas; Vesela, Michaela Michalkova (BioMed research international, 2015)
Recent years have witnessed an increased use of ultrasound in evaluation of the airway and the lower parts of the respiratory system. Ultrasound examination is fast and reliable and can be performed at the bedside and does not carry the risk of exposure to ionizing radiation. Apart from use in diagnostics it may also provide safe guidance for invasive and semi-invasive procedures. Ultrasound examination of the oral cavity structures, epiglottis, vocal cords, and subglottic space may help in the prediction of difficult intubation. Preoperative ultrasound may diagnose vocal cord palsy or deviation or stenosis of the trachea. Ultrasonography can also be used for confirmation of endotracheal tube, double-lumen tube, or laryngeal mask placement. This can be achieved by direct examination of the tube inside the trachea or by indirect methods evaluating lung movements. Postoperative airway ultrasound may reveal laryngeal pathology or subglottic oedema. Conventional ultrasound is a reliable real-time navigational tool for emergency cricothyrotomy or percutaneous dilational tracheostomy. Endobronchial ultrasound is a combination of bronchoscopy and ultrasonography and is used for preoperative examination of lung cancer and solitary pulmonary nodules. The method is also useful for real-time navigated biopsies of such pathological structures.
Keywords: Laryngeal Masks; hlasové řasy; epiglotis; Perioperative Care; ultrasonografie; Tracheostomy; tracheostomie; Trachea; intratracheální intubace; lidé; Ultrasonography; trachea; Vocal Cords; Mouth; nemoci průdušnice; Tracheal Diseases; perioperační péče; laryngální masky; Epiglottis; ústa; High-Energy Shock Waves; rázové vlny s vysokou energií; Intubation, Intratracheal; Humans